A method for preparing a collagen material containing dopamine and iron ions

By using dopamine to coat iron ions in collagen materials, the problems of short hydrolysis time, insufficient antibacterial performance and unsatisfactory hemostatic effect of traditional collagen materials are solved, and the material's hydrolysis resistance, antibacterial performance and hemostatic effect are improved.

CN119746138APending Publication Date: 2025-04-04CENTRAL MEDICAL (HUBEI) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411902502.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When traditional collagen materials face specific biomedical needs, they have short hydrolysis time, insufficient antibacterial performance and poor hemostatic effect.

Method used

Through the optimization of the preparation process, dopamine coated iron ions is used to combine collagen to form a material with a porous spatial structure. The method includes selecting a high-purity collagen powder, dissolving it in ionic water, adding dopamine and ferric chloride solution, adjusting the pH value, then adding glutaraldehyde dropwise, and preparing a dopamine-coated iron ions-coated collagen sponge through a freeze-drying process.

Benefits of technology

It improves the material's hydrolysis resistance, antibacterial properties and hemostatic effect, extends the degradation time of collagen, and enhances its mechanical properties and anti-degradation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746138A_ABST
    Figure CN119746138A_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a collagen material of dopamine-coated iron ions, belonging to the technical field of biomaterials. The material is coated with iron ions by dopamine, and is tightly combined with collagen by cross-linking. The preparation method includes the preparation of a pre-solution, dissolving collagen in water, adjusting the pH value to 2-6 with acetic acid; adding dopamine and iron ions to the solution. Ammonia water is added dropwise again to adjust the pH to 7-8, glutaraldehyde is added dropwise, and a collagen sponge coated with iron ions can be prepared by freeze-drying. The material has a porous structure and a uniform pore size distribution, which can significantly improve the hydrolysis resistance, antibacterial performance and hemostatic performance of the material, and provides more possibilities for the application of the material in the field of biomedical applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomaterials, and more specifically to a method for preparing a collagen material of dopamine coated with iron ions. Background Art

[0002] With the continuous development of biomaterial technology, collagen has been widely used in the medical field due to its good biocompatibility and biodegradability. Collagen can not only support cell attachment and proliferation, but also promote tissue regeneration. However, when facing specific biomedical needs, traditional collagen materials often show defects such as short hydrolysis time, insufficient antibacterial properties, and unsatisfactory hemostatic effects. Therefore, the development of collagen materials with better performance has become one of the current research hotspots.

[0003] Dopamine is widely used in materials science research due to its excellent self-assembly properties. Dopamine can strongly interact with the surfaces of various substrates through chemical reactions, thereby achieving modification and functionalization. In this context, the use of dopamine's chelation of iron ions to coat iron ions provides a new idea for enhancing the functionality of collagen materials. Iron ions have shown good potential in hemostasis and antibacterial applications due to their good biological activity and ability to promote coagulation.

[0004] However, existing collagen materials often face challenges in structural stability and biocompatibility when combined with iron ions. Therefore, developing a new type of collagen material with dopamine-coated iron ions can not only improve the hydrolysis resistance of the material, but also enhance its antibacterial properties and hemostatic effects, which has important theoretical value and application prospects.

[0005] The purpose of the present invention is to solve the above technical problems and to provide a novel method for preparing a collagen material with dopamine coated with iron ions, thereby optimizing the preparation process and improving the overall performance of the material to meet the growing demand for biomedical applications. Summary of the invention

[0006] The purpose of the embodiment of the present invention is to provide a novel method for preparing a collagen material of dopamine-coated iron ions, wherein the collagen material has good biocompatibility and excellent mechanical properties. And because it has a porous spatial structure, it has a high swelling behavior. The introduction of iron ions and dopamine makes the material have good antibacterial and hemostatic properties, providing a new research idea for the application of materials in the field of biomaterials.

[0007] In order to achieve the above object, one of the objects of the embodiment of the present invention is to provide a method for preparing a collagen material containing dopamine coated with iron ions, the method comprising:

[0008] Select high-purity collagen powder or sponge and cut it into pieces. Add 5%-15% by mass into deionized water, heat to 50-60°C, stir thoroughly until completely dissolved to form a uniform collagen solution. Use acetic acid to adjust the pH value of the collagen solution to 2-6 to maintain the colloidal stability and structural integrity of the collagen. Add dopamine and ferric chloride solution, add ammonia water to adjust the pH value to 7-8; add 15% by mass fraction of glutaraldehyde solution. A collagen sponge with dopamine-coated iron ions can be obtained through a freeze-drying process.

[0009] Furthermore, the concentration of the collagen solution is 0.5%-15%.

[0010] Furthermore, the mass ratio of the collagen to dopamine is 100-25:1.

[0011] Furthermore, the concentration of iron ions in the ferric chloride solution is 0.05-0.1 mol / l; the mass ratio of dopamine to iron ions is 20-6:1.

[0012] Furthermore, the pH adjustment is divided into two steps. Before adding dopamine and iron ions, acetic acid is used to adjust the pH to 2-6. The second step is to adjust the pH to 7-8 with ammonia water after adding dopamine and iron ions.

[0013] Furthermore, the dopamine encapsulates the iron ions, and the iron ions are mainly present in the collagen through the chelation effect between dopamine and the iron ions.

[0014] Furthermore, the dopamine and iron ions are chelated, and the dopamine solution can undergo a self-polymerization reaction at a pH of 7-8 to coat the iron ions, and the color of the solution turns black.

[0015] Furthermore, the dopamine and collagen are not mixed together, but are connected to each other through the action of glutaraldehyde.

[0016] Furthermore, the introduction of iron ions can significantly improve the mechanical properties, degradation resistance and certain antibacterial properties of the collagen sponge.

[0017] Furthermore, the collagen sponge can better improve the hemostatic performance of the material after the introduction of dopamine and iron ions.

[0018] Technical effects and advantages of the present invention:

[0019] The invention provides a preparation method of a collagen material with dopamine coated iron ions, belonging to the technical field of biomaterials. The material is coated with iron ions by dopamine, and then closely combined with collagen by cross-linking. The preparation method includes the preparation of a pre-solution, dissolving collagen in water, adjusting the pH value to 2-6 with acetic acid; adding dopamine and iron ions to the solution. Ammonia water is added dropwise again to adjust the pH to 7-8, glutaraldehyde is added dropwise, and a collagen sponge coated with iron ions can be prepared by freeze-drying. The collagen sponge prepared by the present invention has uniform porosity, obvious boundaries between layers, a large spatial structure, and a relatively uniform pore size distribution; the introduction of dopamine provides more binding sites for iron ions, can form coordination bonds with iron ions, and stably coat iron ions. The addition of glutaraldehyde can make collagen and dopamine better combined, and greatly improve the swelling and water absorption and storage capacity of collagen. The introduction of iron ions makes the material have certain antibacterial and hemostatic properties, providing an effective basis for the multifunctional application of the material. At the same time, due to the presence of dopamine and iron ions, the degradation days of collagen, which is originally easily hydrolyzed, are effectively extended, thereby better improving the mechanical properties and anti-degradation properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 This is a flow chart of the collagen material of dopamine coated with iron ions according to an embodiment of the present invention;

[0022] Figure 2 This is a SEM surface image of the collagen material of dopamine coated with iron ions according to Example 1 of the present invention;

[0023] Figure 3 This is a SEM cross-sectional view of the collagen material of dopamine coated with iron ions according to Example 1 of the present invention;

[0024] Figure 4 This is an X-ray diffraction pattern of the collagen material of dopamine coated with iron ions according to Example 1 of the present invention;

[0025] Figure 5 This is a diagram showing the antibacterial effect of the collagen material of dopamine coated with iron ions in Example 1 of the present invention;

[0026] Figure 6 This is a test chart of the hemolysis rate of the collagen material containing dopamine-coated iron ions according to Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with specific implementation methods and examples to specifically describe the embodiments of the present invention, and the advantages and various effects of the embodiments of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementation methods and examples are used to illustrate the embodiments of the present invention, rather than to limit the embodiments of the present invention.

[0028] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the embodiments of the present invention belong. In the event of a conflict, this specification takes precedence.

[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0030] The technical solution provided by the embodiment of the present invention is to solve the above technical problems. The preliminary exploration solutions of the technical solution include:

[0031] 1. The applicant has observed that simple collagen is easily hydrolyzed after being cross-linked with glutaraldehyde, and can usually be completely hydrolyzed in an aqueous solution within a few days to a week. At the same time, the usual cross-linking method will reduce the hydrophilicity of collagen. However, collagen is usually used as a hemostatic material, and reducing its hydrophilicity will weaken its hemostatic effect. This phenomenon limits the application of collagen in the biomedical field, especially in hemostatic materials.

[0032] 2. The applicant mixed dopamine and collagen by simple mixing, which increased the swelling and water absorption properties of the material, but also caused the material to be degraded faster.

[0033] 3. The applicant hopes to improve the hemostatic properties of collagen by introducing other materials, while also improving its resistance to hydrolysis.

[0034] The technical solution provided by the embodiment of the present invention is to solve the above technical problems, and the overall idea is as follows:

[0035] 1. The addition of dopamine will provide more hydrogen bonding sites for collagen. The applicant improves the hydrophilicity of the material by blending collagen and dopamine.

[0036] 2. Dopamine is very easy to self-polymerize under alkaline conditions to generate polydopamine, so before adding dopamine, the pH value of the solution is adjusted to 2-6.

[0037] 3. The use of glutaraldehyde can connect the amino groups of collagen and dopamine through glutaraldehyde, but the pH value of the reaction must be strictly controlled under alkaline conditions, within the range of pH = 7-8.

[0038] 4. In order to better improve the hemostatic effect of the material and change the problem of easy degradation of the material, the applicant added iron ions, which can improve the hemostatic performance of the material. At the same time, the chelation of dopamine, through the analysis of the surface elements of the material, clarified the possibility of iron ions being coated, and the hemostatic effect can be achieved stably. At the same time, the study found that the introduction of iron ions can also improve the hydrolysis resistance of the material by several times.

[0039] The present application will be described in detail below with reference to embodiments and experimental data.

[0040] Example 1

[0041] Select a high-purity collagen sponge and first cut it into small pieces, ensuring that each piece is of uniform size for subsequent dissolution. Then, add the cut collagen into pre-prepared deionized water at a mass fraction of 5%, for example, using a ratio of 1g collagen sponge to 19ml deionized water. Heat the mixed liquid to 50°C while stirring continuously to promote the dissolution of the collagen. Continue stirring until the collagen is completely dissolved to form a uniform and transparent collagen solution.

[0042] Next, acetic acid is slowly added to the collagen solution to adjust the pH value to 2-6, with pH 4.0 being recommended, in order to maintain the colloidal stability and structural integrity of the collagen and prevent it from aggregation or precipitation.

[0043] On this basis, dopamine was added to the collagen solution at a mass ratio of 100:1. Then, 0.05 mlol / l of ferric chloride solution was added to make the mass ratio of dopamine to iron ion solution 6:1 to ensure uniform dispersion. This step can be ensured by stirring to ensure that the two are completely mixed.

[0044] Subsequently, ammonia water was slowly added dropwise to adjust the pH value of the system to 8 to promote the polymerization of dopamine and the cross-linking reaction between collagen. At this time, it can be observed that the solution gradually darkened and turned black, indicating that the polymerization reaction of dopamine was proceeding.

[0045] Next, a 15% mass fraction glutaraldehyde solution (with glutaraldehyde as a crosslinking agent) is added dropwise to the system to ensure that it is evenly distributed. It is recommended that the amount of crosslinking agent added be maintained at 0.5-2% (v / v) to enhance the mechanical strength and hydrolysis resistance of collagen.

[0046] Finally, the reaction mixture is poured into a pre-prepared mold and pre-frozen at -20°C for about 12 hours. After solidification, the finished product is dehydrated by freeze drying, lowering the temperature to -80°C for 24 hours to remove moisture. Finally, a collagen sponge coated with dopamine and iron ions is obtained, which should have a good porous structure and excellent biocompatibility.

[0047] Example 2

[0048] Select a high-purity collagen sponge and first cut it into small pieces, ensuring that each piece is of uniform size for subsequent dissolution. Then, add the cut collagen into pre-prepared deionized water at a mass fraction of 5%, for example, using a ratio of 1g collagen sponge to 19ml deionized water. Heat the mixed liquid to 50°C while stirring continuously to promote the dissolution of the collagen. Continue stirring until the collagen is completely dissolved to form a uniform and transparent collagen solution.

[0049] Next, acetic acid is slowly added to the collagen solution to adjust the pH value to 2-6, with pH 4.0 being recommended, in order to maintain the colloidal stability and structural integrity of the collagen and prevent it from aggregation or precipitation.

[0050] On this basis, dopamine was added to the collagen solution at a mass ratio of 75:1. Then 0.05 mol of ferric chloride solution was added to make the mass ratio of dopamine to iron ion solution 6:1 to ensure uniform dispersion. This step can be ensured by stirring to ensure that the two are completely mixed.

[0051] Subsequently, ammonia water was slowly added dropwise to adjust the pH value of the system to alkaline 8 to promote the polymerization of dopamine and the cross-linking reaction between collagen. At this time, it can be observed that the solution gradually darkened and some turned black, indicating that the polymerization reaction of dopamine was proceeding.

[0052] Next, a 15% mass fraction glutaraldehyde solution (with glutaraldehyde as a crosslinking agent) is added dropwise to the system to ensure that it is evenly distributed. It is recommended that the amount of crosslinking agent added be maintained at 0.5-2% (v / v) to enhance the mechanical strength and hydrolysis resistance of collagen.

[0053] Finally, the reaction mixture is poured into a pre-prepared mold and pre-frozen at -20°C for about 12 hours. After solidification, the finished product is dehydrated by freeze drying, lowering the temperature to -80°C for 24 hours to remove moisture. Finally, a collagen sponge coated with dopamine and iron ions is obtained, which should have a good porous structure and excellent biocompatibility.

[0054] Example 3

[0055] Select a high-purity collagen sponge and first cut it into small pieces, ensuring that each piece is of uniform size for subsequent dissolution. Then, add the cut collagen into pre-prepared deionized water at a mass fraction of 5%, for example, using a ratio of 1g collagen sponge to 19ml deionized water. Heat the mixed liquid to 50°C while stirring continuously to promote the dissolution of the collagen. Continue stirring until the collagen is completely dissolved to form a uniform and transparent collagen solution.

[0056] Next, acetic acid is slowly added to the collagen solution to adjust the pH value to 2-6, with pH 4.0 being recommended, in order to maintain the colloidal stability and structural integrity of the collagen and prevent it from aggregation or precipitation.

[0057] On this basis, dopamine was added to the collagen solution at a mass ratio of 50:1. Then 0.1 mol of ferric chloride solution was added to make the mass ratio of dopamine to iron ion solution 6:1 to ensure uniform dispersion. This step can be ensured by stirring to ensure that the two are completely mixed.

[0058] Subsequently, ammonia water was slowly added dropwise to adjust the pH value of the system to alkaline 8 to promote the polymerization of dopamine and the cross-linking reaction between collagen. At this time, it can be observed that the solution gradually darkened and some turned black, indicating that the polymerization reaction of dopamine was proceeding.

[0059] Next, a 15% mass fraction glutaraldehyde solution (with glutaraldehyde as a crosslinking agent) is added dropwise to the system to ensure that it is evenly distributed. It is recommended that the amount of crosslinking agent added be maintained at 0.5-2% (v / v) to enhance the mechanical strength and hydrolysis resistance of collagen.

[0060] Finally, the reaction mixture is poured into a pre-prepared mold and pre-frozen at -20°C for about 12 hours. After solidification, the finished product is dehydrated by freeze drying, lowering the temperature to -80°C for 24 hours to remove moisture. Finally, a collagen sponge coated with dopamine and iron ions is obtained, which should have a good porous structure and excellent biocompatibility.

Claims

1. A method for preparing a collagen material containing dopamine and iron ions, characterized in that: The method comprises: Select high-purity collagen powder or sponge, cut it into pieces; add 5%-15% by mass into deionized water, heat to 50-60°C, stir thoroughly until completely dissolved, and form a uniform collagen solution; Adjust the pH value of the collagen solution to 2-6; Add dopamine and ferric chloride solution thereto and adjust the pH value to 7-8; Add glutaraldehyde solution dropwise thereto; Dopamine-coated iron ion collagen sponge can be obtained by freeze drying.

2. The method for preparing the collagen material according to claim 1, characterized in that: The concentration of the collagen solution is 0.5%-15%.

3. The method for preparing the collagen material according to claim 1, characterized in that: The mass ratio of the collagen to dopamine is 100-25:

1.

4. The method for preparing the collagen material according to claim 1, characterized in that: The concentration of iron ions in the ferric chloride solution is 0.05-0.1 mol / l; the mass ratio of dopamine to iron ions is 20-6:

1.

5. The method for preparing the collagen material according to claim 1, characterized in that: The pH adjustment is divided into two steps. Before adding dopamine and iron ions, acetic acid is used to adjust the pH to 2-6. The second step is to use ammonia water to adjust the pH to 7-8 after adding dopamine and iron ions.

6. The method for preparing the collagen material according to claim 1, characterized in that: The dopamine coated iron ions make the iron ions mainly exist in the collagen through the chelation effect between dopamine and iron ions.

7. The method for preparing the collagen material according to claim 6, characterized in that: The chelation of dopamine and iron ions, the dopamine solution can undergo a self-polymerization reaction at a pH of 7-8 to coat the iron ions, and the color of the solution turns black.

8. The method for preparing the collagen material according to claim 1, characterized in that: The dopamine and collagen are not present in a mixed manner, but are connected to each other through the action of glutaraldehyde.

9. The method for preparing the collagen material according to claim 1, characterized in that: After the iron ions are introduced, the mechanical properties, degradation resistance and certain antibacterial properties of the collagen sponge can be significantly improved.

10. The method for preparing the collagen material according to claim 1, characterized in that: The collagen sponge can better improve the hemostatic performance of the material after the introduction of dopamine and iron ions.

Citation Information

Cited By

  • Dressing beneficial to relieving pain of burn wound and promoting healing and preparation method thereof

    CN121081709A